Implications of serological, genomic, and epidemiological insights into Mycobacterium tuberculosis mixed infection in a human-managed African elephant (Loxodonta africana) - Ghielmetti, Giovanni; Kerr, Tanya J.; Loubser, Johannes; Hewlett, Jennie; Dippenaar, Anzaan; Loxton, Andre G.; Warren, Robin M.; Goosen, Wynand J.; Miller, Michele A. (Frontiers in Tuberculosis, 2025)
Zoonotic and reverse zoonotic tuberculosis pose a risk to human and animal health, especially when individuals are in close contact. Whole genome sequencing (WGS) has led to significant advancements in our comprehension of bacterial disease dynamics, particularly regarding the transmission of pathogens at the population and individual levels. Mycobacterium tuberculosis was cultured from respiratory samples, including ante-mortem trunk wash, bronchoalveolar lavage, and post-mortem lung tissue samples of one African elephant (Loxodonta africana) euthanized in a South African zoo. The elephant presented with chronic weight loss and lethargy. Animal-side serological testing (Chembio DPP® VetTB for Elephants) conducted on elephant serum yielded a positive result before euthanasia. At post-mortem examination, signs of chronic pneumonia and extensive macroscopic lesions compatible with tuberculosis were observed, confirming the presence of the disease. Genomic DNA was extracted from liquid MGIT culture and an improved culture medium (TiKa) and subjected to WGS analysis. Using a bioinformatic approach, the study identified a mixed infection involving two distinct strains of M. tuberculosis. The predominant strain was classified as lineage 1 and a second strain was identified as lineage 4. Both lineages have been found in a significant proportion of human tuberculosis cases in South Africa. No mutations associated with drug resistance were detected. The report highlights the susceptibility of elephants to human pathogens, particularly in high-burden settings. Biosafety challenges associated with handling and diagnosing tuberculosis in human-managed elephants are reported. We emphasize the importance of implementing effective preventive measures to ensure the safety of both humans and animals in zoo environments. Finally, the importance of multiple sampling and analysis of within-host mycobacterial populations for investigations of transmission is demonstrated.